2018
DOI: 10.1108/bfj-03-2018-0206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-congruity (symbolic and functional) on the brand hate

Abstract: Purpose The purpose of this paper is to test the impact of symbolic and functional incongruity on brand hate. According to self-congruity theory, symbolic and functional congruence are a critical phenomenon in consumer buying decisions. Therefore, the present study develops a theoretical framework based on self-congruity theory to examine the key determinants of brand hate. Design/methodology/approach Data were collected only in fast-food chain franchises in the capital city territory of Pakistan. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 94 publications
6
127
0
3
Order By: Relevance
“…Generally, the economic condition of people is the main cause, which will change the attitudes of local people. A previous study has confirmed that the economic growth of citizens is the main reason to support a project (Islam et al, 2019;Ko & Stewart, 2002) if it economically benefits the local citizens. Considerable support for a project comes from the local community.…”
Section: Local Citizens' Benefits Support For Cpec Developmentmentioning
confidence: 90%
“…Generally, the economic condition of people is the main cause, which will change the attitudes of local people. A previous study has confirmed that the economic growth of citizens is the main reason to support a project (Islam et al, 2019;Ko & Stewart, 2002) if it economically benefits the local citizens. Considerable support for a project comes from the local community.…”
Section: Local Citizens' Benefits Support For Cpec Developmentmentioning
confidence: 90%
“…In line with earlier research ( Van der Kaap-Deeder et al, 2016 ), distinctive brand attributes promote positive outcomes, i.e., satisfaction, loyalty, and brand equity. Similarly, in the dairy sector, acceptance of a brand does not merely depend on taste, but on other factors as well, for instance, other intangible and tangible attributes of brands such as unique positioning, which can result in increased brand equity ( Islam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result can be achieved with the help of advertisements that visualize consumer personalities to make them feel their existence a congruity between them and the brands. In a Pakistani context, the role of symbolic congruity between customers and brands is highlighted in the literature (Islam et al, 2019). From a social identity perspective, the advertisements that focus on demonstrating consumers as seeking in-group identity through the consumption of brands can strengthen consumer-brand ties.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…In countries such as Pakistan, the rural market represents 64% of the total population (The Express Tribune, 2017). Rural consumers have discretionary income coupled with aspirations to purchase brands (Dev et al, 2018) but the brand management literature by large represents consumer-brand emotions of individuals living in metro cities of Pakistan (Islam, Attiq, Hameed, Khokhar, & Sheikh, 2019). The emotions and attitudes of the rural consumer of apparel brands need greater attention, which also indicates a clear gap within the literature.…”
Section: Introductionmentioning
confidence: 99%